Assessment of children`s psychomotor development in the remote period after aortic arch reconstruction with antegrade cerebral perfusion - Y. P. Truba; L. M. Tkachenko; R. I. Sekelyk; I. V. Dzyurii; V. V. Lazoryshynets (Клінічна хірургія)
Objective. To evaluate the psychomotor development of children after aortic arch reconstruction in the conditions of selective antegrade cerebral perfusion.